Pop culture and the dark side of the American dream: con men, gangsters, drug lords, and zombies - Cantor, Paul A. (University Press of Kentucky, 2019)
Aristocracy in America: Huckleberry Finn and the democratic art of imposture -- The talented Mr. Dukenfield: W.C. Fields and the American dream -- "I believe in America": the Godfather films and the immigrant's tragedy -- The Macbeth of meth: Breaking bad and the tragedy of Walter White -- The apocalyptic strain in popular culture: the American nightmare becomes the American dream.